Sources of information value : - Ricart-Costa, Joan E. (Palgrave Macmillan, 2004)
This book provides a conceptual framework to understand and analyze the decline of the telecommunications industry and the rise of information industries. This includes information distribution, banking, advertising, computing, etc. and will use a value-based perspective to show the industry shaping dynamics. The integrative framework will cover issues relevant to all information industries including network externalities, lock in and switching costs, cost structure analysis, transactions costs and infomediaries.